2019
DOI: 10.1111/jce.14300
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological parameters and anatomical evaluation of left bundle branch pacing in an in vivo canine model

Abstract: Introduction: Left bundle branch pacing (LBBP), a form of conduction system pacing in addition to His bundle pacing (HBP), can potentially maintain left ventricular electrical synchrony with better sensing and a low and stable capture threshold. Methods:We performed both HBP and LBBP using a canine model (n = 3; male;weight 30-40 kg). The electrocardiogram (ECG), intracardiac electrogram characteristics, and pacing parameters were compared between HBP and LBBP. The hearts were isolated and stained by Lugol's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The capture thresholds computed were close to the range of those observed clinically [18]- [23], although a bit low. We presented most results for a pulse of 1 ms duration while 0.5 ms is often used [23].…”
Section: A Capture Thresholdssupporting
confidence: 56%
“…The capture thresholds computed were close to the range of those observed clinically [18]- [23], although a bit low. We presented most results for a pulse of 1 ms duration while 0.5 ms is often used [23].…”
Section: A Capture Thresholdssupporting
confidence: 56%
“…New onset BBB developed frequently after TAVR or SAVR and associated with increased early and late all‐cause mortality 6 . It has been demonstrated that patients with typical‐BBB morphology could benefit from LBBP in terms of QRS correction 23,24 . In the present study, BBB correction via LBBP succeeded in all the four patients complicated with BBB after TAVR or SAVR with a low and stable capture threshold during follow‐up.…”
Section: Discussionsupporting
confidence: 55%
“…LBB is a wide network beneath the endomyocardium of the left septum (18). Thus, positioning of the lead at this area could easily capture the left conduction system (8). In case of lead dislodgement and perforation, repositioning of the lead to a distal LBB area could probably prevent the recurrence of these complications because the original area might be injured by the lead, and the fixation of lead in posterior septum through the C315 His sheath is simple.…”
Section: Lead Dislodgement and Septum Perforationmentioning
confidence: 99%
“…However, as a novel pacing technique, the safety of LBBP has not been well-documented. To capture the left conduction system, the LBBP lead should be screwed deep enough into the subendomyocardium of the left ventricle (8), which differs from the conventional right ventricular (RV) pacing lead. Consequently, unique procedure-related complications, such as interventricular septum perforation, lead dislodgement, septum injury, and lead fracture, of LBBP are observed.…”
Section: Introductionmentioning
confidence: 99%